Smart Digital Youth: Digital Literacy and Cyber Law Awareness Training for Youth - Daud, Rosy Febriani; Falinda, Novia Sri; Mustika, Tiara (TAAWUN, 2026)
This Community Service activity aims to improve digital literacy and cyber law awareness among adolescents in Mentosari Village, Batang Regency, to develop intelligent, ethical, and law-abiding digital citizens. The implementation method for the activity includes needs analysis, preparation of training materials, delivery through classroom sessions, direct practice, interactive discussions, case simulations, and evaluation using pre- and final tests. The training participants consisted of adolescents aged 13–21 who actively use social media and digital devices. The activity results showed a significant increase in participants’ understanding of digital literacy, cybersecurity, media ethics, and basic knowledge of the Information and Electronic Transactions Law. Participants were able to identify digital risks, implement account security measures, and understand the legal consequences of irresponsible digital activities. The training also raised adolescents’ awareness of the importance of being responsible and character-based digital citizens. Contributing to this activity successfully strengthened adolescents’ ability to use technology in a healthy, safe, and responsible manner, and provided a sustainable basis for adolescent activities to contribute to the formation of a positive digital environment in Mentosari Village.